Монгол Улсын Үндсэн хуулийн нэмэлт өөрчлөлтийн асуудалд - Д.Болд-Эрдэнэ (Politology, 2023)
There are two attitudes in constitution of Mongolia that being sustainable and innovations. Nowadays required to make difinitive change in the constitution. But we need to make this change seriously, not emotionally. About it we considered some articles in this speech.